P317 Diagnostic yield of EUS-FNA in UGI submucosal lesions- experience from a non-tertiary centre in UK. (19th June 2022) - Sethia, Rahul; Elzubier, Mohamed; Dasgupta, Kaushik; Hancock, John; Mitra, Vikramjit
Abstract : Introduction: EUS guided tissue acquisition is a well established investigation to confirm the histopathological diagnosis for submucosal lesions in upper gastrointestinal tract. The European Society of Gastrointestinal Endoscopy (ESGE) and Joint Advisory Group (JAG) suggests the frequency of obtaining a diagnostic tissue sample of at least 85% for EUS-FNA (1). The aim of this study was to determine the diagnostic adequacy and safety of EUS guided tissue acquisition in submucosal lesions. Methods: We carried out a retrospective audit of all patients (identified from endoscopy and pathology database) who underwent EUS guided tissue acquisition between 1st October 2019 and 30th November 2021. Data collected include patient demographics, cross-sectional imaging, cytopathological diagnoses, treatment modality, complications and 30-day procedure related mortality. Final diagnoses were confirmed from EUS biopsy, surgical resection specimen or cross-sectional imaging (discussed in a MDT setting if histology negative). Results: 39 patients [mean age 66.7 years, 36.8% females] underwent 39 EUS-FNA procedures (18 and 21 patients had a cancer and benign diagnosis respectively). 33 (85%) samples were deemed adequate for analysis by the cytopatholgist (5 diagnosed as lipoma on EUS appearance and 1 diagnosed as GIST on CT/EUS appearance under surgical follow up). Sensitivity, specificity, diagnostic accuracy, positive predictive value (PPV) and negative predictive value (NPV) were 94.8%, 100%, 85%, 100%, and 94.1% respectively. There was no procedure related complications or mortality. Histopathological diagnoses of cancer on EUS biopsy (n=17) – GIST (14), Schwanomma (1), Granular cell tumor (1), Adenocarcinoma (1). Conclusions: This study confirms that EUS-FNA of submucosal lesions can be highly effective and safely carried out. Overall adequacy of tissue acquisition is in compliance with ESGE & JAG guidelines. Our diagnostic yield is in in keeping with the published literature.